PENGELOLAAN PASAR DAYANG SURI OLEH DINAS PERDAGANGAN DAN PERINDUSTRIAN KABUPATEN INDRAGIRI HILIR TAHUN 2017-2020 - Mhd Hendra Wahyuda (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The market serves as a place or container for services for the community, the market if managed properly will be able to increase the original income of the area, this also applies to the Dayang Suri Tembilahan Market, this research is motivated by the unmanagement of Dayang Suri Market by the Department of Trade and Industry of Indragiri Regency Downstream seen from planning both physical and non-physical planning, market support facilities and Standard Operating Procedures have not been running as they should. The results of this study are that the Management of Dayang Suri Market by the Department of Trade and Industry of Indragiri Hilir Regency has not been managed properly because both of the physical planning which includes building facilities such as kiosks and stalls in a damaged and abandoned condition, the existing standard operating procedures have not been implemented. properly. The factors that become obstacles in market management include, a special budget for Dayang Suri Market does not yet exist, geographical conditions, inadequate facilities, and a one-stop market management model. Keysword: Management, Traditional Market